Early diastolic strain rate and its associations with estimated glomerular filtration rate and albuminuria. (3rd October 2022) - Landler, N; Olsen, F J; Bro, S; Feldt-Rasmussen, B; Hansen, D; Kamper, A L; Christoffersen, C; Ballegaard, E L F; Soerensen, I M H; Bjergfelt, S S; Seidelin, E; Biering-Soerensen, T
Abstract: Background: The ratio of early diastolic inflow to early diastolic strain rate, E/e'sr, is a novel echocardiographic measure, which has been shown to correlate better with left ventricular (LV) filling pressures than the conventionally used measure, E/e' (1). Additionally, E/e'sr has demonstrated prognostic value in various patient populations (2). Patients with chronic kidney disease (CKD) suffer frequently of diastolic dysfunction and elevated filling pressures (3). We wanted to investigate, how E/e'sr associates with two central measures of kidney function: estimated glomerular filtration rate, eGFR, and urine albumin creatinine ratio, UACR. Methods: We enrolled a cohort of 825 ambulatory patients with CKD at the Departments of Nephrology of two university hospitals. Participants were examined with echocardiography including tissue doppler imaging. Two-dimensional speckle strain analysis was performed in all three apical standard projections. LV mass index (LVMI), E/e' and global longitudinal strain (GLS) were determined according to guidelines (4, 5). Global early diastolic strain rate, e'sr, was calculated as the average of all 18 segments and indexed to early transmittal inflow velocity in order to calculate E/e'sr. Multivariable linear regression models were used to investigate associations between e'sr, E/e'sr, E/e' and kidney parameters. Models were adjusted for eGFR, UACR, LV ejection fraction (LVEF), age, sex, ever smoker, diabetes, hypertension, systolic and diastolic blood pressure (BP), heart rate and body mass index (BMI). We performed sensitivity analysis by excluding patients with known coronary artery disease (CAD) and heart failure (HF). Results: Seventy-six patients had no measures of E/e'sr available leaving 749 for analysis. Excluding patients with CAD and/or HF (n=88) left 661 patients. For clinical and echocardiographic variables, see table. Patients with lower e'sr were older, had higher blood pressure and lower LVEF and GLS. E'sr was independently associated with eGFR and decreased 0.014 s –1 (95% CI 0.006 to 0.022, p=0.002) pr. 10 mL/min/1.73 m 2 decrement of eGFR. Similarly, E/e'sr increased 1.1% (95% CI 0.2% to 19.2%) pr. 10 mL/min/1.73 m 2 decrement of eGFR indicating rise in LV filling pressures. Contrary, E/e' was not independently associated with eGFR (p=0.5). Sensitivity analysis did not change the results significantly. None of the three measures were independently associated with UACR. Cubic restricted splines of e'sr, E/e'sr, E/e' over eGFR (figure) showed a non-linear relationship between E/e'sr and eGFR with accelerated increase at eGFR below 40 ml/min/1.73 m 2 . Conclusion and perspectives: In patients with CKD, deformation-based e'sr and E/e'sr are independently associated with eGFR, but not with UACR. Repeated measurements and longitudinal follow-up of the cohort will provide information on the prognostic performance of these novel measures compared with conventional measures of LV filling pressure. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Capital Region of Denmark